2021
DOI: 10.3389/fvets.2021.691196
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of microRNA From Peripheral Blood of Dairy Cows in Response to Staphylococcus aureus-Infected Mastitis

Abstract: As the main pathogen causing dairy cow mastitis, Staphylococcus aureus can cause subclinical mastitis, which is difficult to be diagnosed. It seriously affects milk quality and the economic benefits of the dairy industry. Therefore, it is very necessary to find biomarkers for early diagnosis of S. aureus-infected mastitis in peripheral blood of dairy cows. In this study, S. aureus was used to infect the mammary gland tissues of dairy cows, and a mastitis model was successfully constructed. The RNAseq technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…Additionally, 29 top-expressed miRNAs account for 81, 84, 83, and 85% in the expression of total miRNAs at 0, 4, 8, and 12 h cells, respectively (Figure 4), which are similar to the previous results in bovine MAC-T cells challenged with E. coli or S. aureus (16). The expression of bta-miR-21-5p_R-1 is more than 30% in total miRNAs and is the highest one (Figure 4), which is also in line with the result in primary bMECs (15), while bta-miR-21-5p_R-1 is not the highest expressed miRNAs at peripheral blood in Chinese Holstein cows (23,24), bovine milk-derived exosomes (22), bovine milk (21), and bovine mammary glands (19). This indicated that bta-miR-21-5p_R-1 was the unique and essential miRNA to maintain the function of bMECs.…”
Section: An Overview Of Mirna Profilesupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, 29 top-expressed miRNAs account for 81, 84, 83, and 85% in the expression of total miRNAs at 0, 4, 8, and 12 h cells, respectively (Figure 4), which are similar to the previous results in bovine MAC-T cells challenged with E. coli or S. aureus (16). The expression of bta-miR-21-5p_R-1 is more than 30% in total miRNAs and is the highest one (Figure 4), which is also in line with the result in primary bMECs (15), while bta-miR-21-5p_R-1 is not the highest expressed miRNAs at peripheral blood in Chinese Holstein cows (23,24), bovine milk-derived exosomes (22), bovine milk (21), and bovine mammary glands (19). This indicated that bta-miR-21-5p_R-1 was the unique and essential miRNA to maintain the function of bMECs.…”
Section: An Overview Of Mirna Profilesupporting
confidence: 90%
“…Characterization of the transcriptomic response to infection in different tissues is an effective approach to understanding the response mechanism of dairy mastitis. In the past decades, a large number of mastitis-related mRNAs and miRNAs have been identified by the Transcriptome-Seq in infected bMECs (9,(15)(16)(17), udder tissues (18)(19)(20), milk whey (21), milkderived exosomes (22), whole blood (23)(24)(25) and blood-isolated monocytes (26) in the context of S. aureus, Streptococcus uberis, Streptococcus agalactiae, and E. coli. MECs have a strong capacity to mount differing innate immune responses to gram-positive and gram-negative bacterial challenges in their own way.…”
Section: Introductionmentioning
confidence: 99%
“…The Wnt pathway consists of a large family of highly conserved glycoproteins that cross-talk with MAPK in development, determining cell fate, tissue regeneration, and maintaining tissue homeostasis ( Zhang et al, 2014 ). Previous studies have shown that Wnt and MAPK pathways are essential for normal mammary gland development ( Roarty and Serra, 2007 ; Li et al, 2018 ) and are involved in immune system-related signaling pathways ( Luoreng et al, 2021 ). These studies reported candidate miRNA including bta-miR-19a, bta-miR-19b, bta-miR-21-5p, bta-miR-29c, bta-miR-143, bta-miR-145, and bta-miR-146b are associated with Wnt signals and MAPK pathway ( Li et al, 2018 ; Luoreng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cow mastitis is an inflammatory disease of mammary tissue. Often, it is caused by the invasion and proliferation of pathogenic microorganisms, physical damage, chemical stimulation and the cow's immune response (1,2,37). However, among these causes, E. coli is the most common culprit (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Mastitis is one of the most common diseases in dairy cows worldwide, causing damage to mammary tissue, reduces milk production, decreases the quality of dairy products, and increases mortality and culling rates (1,2). Although mastitis is a common disease, it is both expensive and difficult to treat, resulting in huge losses in the dairy industry (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%